Nuts about macadamia - Paap, Peter (Technical Centre for Agricultural and Rural Cooperation, 2006)
Producing less, but selling for more. That, in a nutshell, is the new philosophy being embraced by farmers in Burundi, who are launching themselves headlong into diversification.